Satisfaction of family physician team members in the context of contract system: A cross-sectional survey from Shandong Province, China - Cai, Weiqin; Du, Yuanze; Gao, Qianqian; Gao, Runguo; An, Hongqing; Liu, Wenwen; Han, Fang; Jing, Qi; Wang, Chunping (Frontiers in Public Health, 2022)
Background Family physicians play a key role in responding to the growing demand for primary healthcare due to aging. The work attitude of family physician team members (FPTMs) impacts their work efficiency and quality. Knowing how satisfied they are with their jobs can help identify potential directions and entry points for incentives. The purpose of this study is to analyze the job satisfaction status and influencing factors of grassroots health service personnel after the implementation of the family physician contract system in China. Methods The study conducted a cross-sectional survey with 570 FPTMs in three prefecture-level cities in the Shandong Province. Satisfaction was measured using 30 items across seven dimensions. Responses were recorded on a 5-point Likert scale. Descriptive statistical analysis was used to analyze the general information and satisfaction of FPTMs. Multiple linear regression analysis was used to analyze the factors influencing job satisfaction. Results The overall job satisfaction among FPTMs was not high. Among the seven dimensions, interpersonal relationships had the highest satisfaction (4.10 ± 0.78), while workload had the lowest satisfaction (3.08 ± 0.56). The satisfaction levels of the three sample regions were different, and the results were opposite to their regional economic development levels. The results of the multifactor analysis showed that gender, income level, educational background, working years, daily working hours, number of training sessions per year and the proportion of performance pay had significant impact on overall job satisfaction. Conclusions The development of a family physician contract system has increased the workload of FPTMs. In addition to the implementation of the new policy, attention should be paid to the workload and working attitude of family physicians. The fundamental measures should focus on attracting more personnel to work at the grassroots level by accelerating education and training to solve the problem of insufficient health personnel at the grassroots level. Simultaneously, attention should be paid to the improvement of the medical staff's salary level and the need for self-promotion, such as training.